Pemanfaatan Jurnal Ilmiah oleh Mahasiswa Akuntansi Universitas 17 Agustus 1945 (UNTAG) Surabaya: Studi Kualitatif tentang Kebiasaan dan Tantangan - Paulino da Costa Ferreira; Hwihanus Hwihanus (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
This study aims to explore the habits and challenges faced by accounting students at Universitas 17 Agustus 1945 (UNTAG) Surabaya in utilizing academic journals as reference materials for their studies. The research employed a qualitative approach using in-depth interviews as the main method of data collection. The findings reveal that while students are aware of the importance of academic journals, they face several challenges, including limited access, lack of skills in finding relevant journals, and difficulties in understanding English-language content. The results provide insights that could enhance the accessibility and use of academic journals among students.